Distribution features of the rats’ major salivary glands cells glycoproteins during early postnatal period after antenatal antigen action - Syrtsov, V. K; Maslova, I. N.; Сирцов, Вадим Кирилович; Маслова, Ірина Миколаївна (My University, 2014)
Background. Nowadays, in the diseases’ structure, according to literature data, one of the leading place take pathological condition connecting with the salivary glands’ inflammatory and dystrophic disorders. The problem of etiology and pathogenic not enough studied and demanded intent attention of researchers. Objective. The purpose was to determine the features of glycoproteins’ distribution in the structures of rats’ major salivary glands in early postnatal period after intrauterine antigen action. Methods. The object of the research was 224 salivary glands of white laboratory rats. Due to impossible quality materials’ taking in the early periods of postnatal life parotid and sublingual salivary glands, the investigation done at the gl. submaxillaris. The histochemical exposure and differentiation of carbohydrate compounds conducted by means of PAS-staining technic. For fermentative control used diastase. The results of histochemical exposure of glycoproteins stain were done by semi-quantitative. Results. In newborn animals receiving antigen in the antenatal period, in the cells’ cytoplasm indicate the accumulation’ increase of PAS-positive compounds retained until the 14th and offset at the 45th day of postnatal life. The detected changes in the major salivary glands cells’ are the basis for the development of inflammatory and dystrophic processes and can lead to the functional violations formation’ hereinafter. Conclusion. Our findings indicate that at the background of intrauterine antigen action, the glycoproteins’ accumulation intensity in parenchymal and stromal cells’ cytoplasm of the major salivary glands is decrease, but glycogen content is increase compared with intact animals group. Furthermore, we detected cells’ secretory activity reduction from 1st to 14th day of postnatal life with increase glycogen’ accumulation in the cells’ cytoplasm. That revealed changes offset at the 45th day after birth in all animals group. Мета роботи – встановити особливості розподілу глікопротеїнів в клітинах великих слинних залоз в ранньому постнатальному періоді після внутрішньоутробної антигенної дії. У новонароджених тварин, що отримали антиген в антенатальному періоді, в цитоплазмі клітин виявлено зниження накопичення ШЙК-позитивних сполук, яке зберігається до 14-ї та нівелюється на 45-ту добу. Виявлені зміни в клітинах великих слинних залоз є підґрунтям для розвитку запальних та дистрофічних процесів в слинних залозах, що, в подальшому, може призвести до виникнення різних функціональних порушень.
Особливості розподілу глікопротеїнів в клітинах великих слинних залоз щурів в ранньому постнатальному періоді після антенатальної антигенної дії
Keywords: major salivary glands; parenchymal cells; stromal cells; intrauterine antigenic action; glycosaminoglycans; the rats; великі слинні залози; клітини строми; клітини паренхіми; внутрішньоутробна антигенна дія; глікопротеїни; щури